Indigenous knowledge on host tree preference of the wild edible Gynanisa maja (Lepidoptera: Saturniidae) matches with the laboratory test results in western Zambia - Chanda, Benjamin; Olweny, Calleb Ochia; Chungu, Donald (African Journal of Agricultural Research, 2022)
Gynanisa maja is an edible caterpillar and contributes significantly towards household food security. The linkage between indigenous and scientific knowledge influencing G. maja forage preference is not yet clear, and therefore the study aimed at determining this linkage regarding host preferences for G.maja in western Zambia. A household survey was conducted to determine people’s perception on the most preferred host plants and in order to compare with the laboratory tests, phytochemical and proximate analyses on host plants were conducted. Local people (100% of the respondents) mentioned that G. maja frequently feed on Julbernadia paniculata than on any other tree in the area. Both phytochemical and proximate analyses showed that J. paniculata had significantly high amount of total ash (F2.15 = 557.0, p < 0.001) and crude protein (F2.15 = 77.6, p < 0.001) and low content of total fat. The presence of terpenoids and lack of saponins and phenols in J. paniculata provided further support that J. paniculata is the most preferred host for G. maja. Study findings lays a foundation for embarking on farming G. maja using J. paniculata which will consequently enhance household food security.
Keywords: Edible Caterpillar; Forage Preference; Plant Nutrients; Phytochemicals; Indigenous Knowledge